MENGKAJI LEGALITAS PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2012 TENTANG PENYESUAIAN BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAM KUHP - Mohamad Rifki (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2018)
Besides court function, the Supreme Court also has rule function, counseling function, supervisor function, and administrative function. Judges as an organ on Supreme Court must be differentiated with Supreme Court as a State Institution. Judges can be a law maker on their verdict (Judge made-law), because Judges are not only a mouthpiece of the law (la bouche de la loi), instead they also considered to know the law (Ius Curia Novit). However, the Regulation of Supreme Court as an implementation of its rule function can’t be stated as a law making (rechtsvinding), because the Regulation of Supreme Court is not a part of Law Making, but rather Rule Making. Regulation of Supreme Court Number 2 Year 2012 about Adjustment on the Limitation of Minor Crime and Fine on KUHP is one of the regulation that has been made by the Supreme Court as a State Institution. This article will analyze the legality of the Regulation of Supreme Court based on the authority given by the act or constitution, and also analyze it from the regulation concerning the drafting of act.